COMPARATIVE STUDY BETWEEN JIGSAW TECHNIQUE AND COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) IN READING COMPREHENSION - RAHMAT HUDA (Linguistik : Jurnal Bahasa dan Sastra, 2019)
AbstractThe aim of this research was to compare Jigsaw technique and Cooperative Integrated Reading and Composition (CIRC) in reading comprehension of the VIII grade at SMP Negeri 1 Muarasipongi. This research conducted by quantitative method and it was an experimental type. The population of the research were the grade VIII students that consist of 247 students. But the writer only took 64 students as sample of this research as random sampling. The total number of sample divided into two groups; they were 32 students as an experimental group and 32 students as a control group. The data conducted by the instrument of research that contained of essay test. In testing the hypothesis and analyzed the data of the research, it analyzed with the  t-test formula. Based on the calculation above, it can be known that the coefficient of to= 3,51. It is compared with the score of tt on degree freedom (df) 70 or (32+32-2) = 62 is 2,00. So, the score of to is larger than the score of to namely, 3,51 > 2,00. Dealing with calculation, it can be concluded that the hypothesis is accepted. So, Jigsaw technique is better than CIRC in Reading Comprehension of the VIII Grade of SMP Negeri 1 Muarasipongi in 2016-2017 Academic Year.Keywords: Jigsaw, CIRC, Reading ComprehensionCOMPARATIVE STUDY BETWEEN JIGSAW TECHNIQUE AND COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) IN READING COMPREHENSION